PENGARUH PENGETAHUAN ANGGOTA TENTANG KOPERASI DAN KUALITAS PELAYANAN TERHADAP PARTISIPASI ANGGOTA PADA KOPERASI TAHU TEMPE INDONESIA (KOPTTI) SARI JAYA KOTA PEKANBARU - Ariantoso, Topit; Gusnardi, Gusnardi; Mujiono, Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effect of members' knowledge about cooperatives and service quality on member participation in Koopersi Tahu Tempe Indonesia (KOPTTI) Sari Jaya Kota Pekanbaru. This research is a research based on the philosophy of quantitative positivism, the population of this study is 35 respondents and the population is taken as a saturated sample (census technique). Data collection techniques using documentation and questionnaires. Data analysis using multiple regression analysis. The results of this study indicate that members' knowledge has an effect on member participation, service quality has an effect on member participation and member knowledge and service quality has an effect on member participation.Keywords: Member Knowledge, Quality of Service, Member Participation